Development of an Enhanced Predictive Model for Road Accident Occurrence in Nigeria - Chukwudi Ugbaja; Friday E. Onuodu; Henry Onyebuchukwu Ordu; Emmanuel J. Izionworu (Yayasan Literasi Sains Indonesia, 2026)
Road accidents in Nigeria rank as the second highest globally, with 33.7% of deaths per 100,000 persons occurring annually. This study developed and tested a predictive model for road accident occurrence using Artificial Neural Networks (ANN) to address the technological gap in Nigeria's road safety management systems. A feed-forward neural network architecture comprising 52 input neurons, three hidden layers (32, 16, and 8 neurons) with ReLU activation, and a single sigmoid output neuron was designed. Dropout (0.3, 0.3, 0.2) and L2 regularization (0.001, 0.001, 0.0005) were incorporated to address sample size constraints. The dataset comprised 2,847 records from FRSC, NEMA, and NBS (2018-2023) across twelve Nigerian states, with 24 features spanning road, environmental, driver, and vehicle factors. Stratified random splitting yielded 1,994 training, 570 validation, and 283 temporally distinct test records. The model achieved 84.5% accuracy (95% CI: 79.8%-88.5%), 77.0% recall, 89.4% specificity, and 0.89 AUC on independent test data—a 13.5 percentage point improvement over the existing K-modes system (p<0.0001). Five-fold cross-validation confirmed stability (84.3%±0.6%). Feature importance analysis identified speeding (18.4%), alcohol impairment (15.2%), wet roads (11.8%), night driving (9.4%), and lane discipline (8.1%) as dominant predictors, with human factors accounting for 45.3% of predictive power. This study provides the first evidence-validated ANN-based accident prediction model calibrated for Nigeria, establishing a reproducible methodological template for developing contextually-adapted predictive systems in data-constrained environments while demonstrating statistically significant and practically meaningful improvement over existing approaches.